Preparation and unequivocal identification of the regioisomers of nitrocatechol monobenzyl ether. Issue 16 (18th August 2017) - Bolchi, Cristiano; Bavo, Francesco; Pallavicini, Marco
ABSTRACT: The four positional isomers of nitrocatechol monobenzyl ether were prepared as intermediates to nitrobenzodioxanes directly from 2-benzyloxyphenol or, through two-four steps, from catechol. These preparations addressed the issue of the certain identification of the nitration products prescinding from chemical correlation to the synthetic precursors because the positional isomers are very similar for some properties and analytical data available from the literature are largely incomplete and not conclusive. The here provided NMR, DSC, and acidity data unequivocally distinguish each nitrocatechol monobenzyl ether from its regioisomers. GRAPHICAL ABSTRACT: